Monocytic Myeloid-Derived Suppressor Cells Inhibit Myofibroblastic Differentiation in Mesenchymal Stem Cells Through IL-15 Secretion - Cheuk, Yin Celeste; Xu, Shihao; Zhu, Dong; Luo, Yongsheng; Chen, Tian; Chen, Juntao; Li, Jiawei; Shi, Yi; Zhang, Yi; Rong, Ruiming (Frontiers in Cell and Developmental Biology, 2022)
Background: Accumulating evidence indicates that mesenchymal stem cells (MSCs) are precursors of myofibroblasts, which play a vital role in renal fibrosis. The close interaction between MSCs and other immune cells regulates the development of multiple fibrosis-related diseases. However, the effect of myeloid-derived suppressor cells (MDSCs) on MSCs remains unexplored. Here, we investigated the effect of MDSCs on the myofibroblastic differentiation of MSCs. Methods: MSCs were induced to undergo myofibroblastic differentiation with transforming growth factor beta 1 (TGF-β1). M-MDSCs and G-MDSCs were sorted by flow cytometry. Supernatants derived from MDSCs were administered to cultured bone marrow MSCs (BM-MSCs) undergoing TGF-β1-induced myofibroblastic differentiation. Myofibroblastic differentiation was evaluated by immunostaining. The expression of fibrosis-related genes was determined by quantitative PCR and western blot analysis. In vitro, M-MDSC supernatant or M-MDSC supernatant with interleukin (IL)-15 mAbs was administered following unilateral renal ischemia-reperfusion injury (IRI) to observe the myofibroblast differentiation of renal resident MSCs (RRMSCs) in a murine model. Results: Myofibroblastic differentiation of MSCs was hindered when the cells were treated with MDSC-derived supernatants, especially that from M-MDSCs. The inhibitory effect of M-MDSC supernatant on the myofibroblastic differentiation of MSCs was partially mediated by IL-15-Ras-Erk1/2-Smad2/3 signaling. Treatment with M-MDSC supernatant ameliorated renal fibrosis and myofibroblastic differentiation in RRMSCs through IL-15. Additionally, M-MDSC supernatant increased M-MDSC infiltration in the kidney in a mouse IRI model. M-MDSC supernatant downregulated the adhesion and migration marker CD44 on the cell membrane of MSCs via IL-15. Conclusion: M-MDSC-derived supernatant inhibited the TGF-β1-induced myofibroblastic differentiation of MSCs through IL-15. Our findings shed new light on the effect of MDSCs on myofibroblastic differentiation and adhesion of MSCs, which might provide a new perspective in the development of treatment strategies for renal fibrosis.